STUDY ON MARSHAL CHARACTERISTICS AND RESIDUAL STABILITY DURING VARIATIONS IN SOAKING TIME OF AC-WC ASPHALT MIXTURES DUE TO THE ADDITION OF LDPE PLASTIC AGGREGATES - Putra Havia, Rafeiza Rizki; Budirahardjo, Slamet; Wardani, Agustina (Science and Technology Research Centre, Universitas PGRI Semarang, 2026)
This study aims to analyze the Marshall characteristics and retained stability of Asphalt Concrete-Wearing Course (AC-WC) mixtures incorporating Low-Density Polyethylene (LDPE) plastic with variations in immersion duration. The research was motivated by the premature deterioration of pavement structures caused by water infiltration and the quality of asphalt mixtures. An experimental laboratory method was employed in accordance with the 2018 General Specifications of Bina Marga, including the determination of the Optimum Asphalt Content (OAC), specimen preparation, and Marshall as well as retained stability testing with immersion periods of 1 and 4 days and LDPE contents of 6%, 9%, and 12%. The results indicated an Optimum Asphalt Content (OAC) of 5.88%. The highest stability values were obtained from the mixture containing 12% LDPE, reaching 2360.23 kg after 1 day of immersion and 1936.87 kg after 4 days of immersion. Flow values and volumetric parameters (VIM, VMA, and VFA) generally satisfied the specification requirements. The highest retained stability values reached 96.0% for the 1-day immersion period and 104.5% for the 4-day immersion period, while the lowest value was 84.0%. Although stability decreased with increasing immersion duration, most mixtures still met the minimum specification requirements. It can be concluded that the incorporation of LDPE into AC-WC mixtures enhances Marshall characteristics and improves resistance to water-induced damage.